Arachnophobia and early English literature - Cavell, M (Boydell and Brewer, 2018)
In view of their great variety, numbers and pervasiveness in everyday life, the impact of spiders in any given cultural climate cries out for investigation. While the abundance of spiders makes them central to the study of ecology and evolution, their commonness and long collective lifespan also position them as prime material for historical discussion. It is, however, these creatures’ literary potential that stands out in the above-quoted ecologist’s metaphor. As a highly resilient family, spiders would likely have been as common in early and high medieval England as they are today, making encounters between them and the human communities responsible for our surviving texts certain. How much did the common presence of spiders in quotidian contexts influence writers in this period? One of this article’s aims is to address this question, by surveying the background to and instances of spider imagery in Old and early Middle English, with reference to biblical, medical, philosophical, penitential, homiletic, hagiographic, and bestiary texts.